1991
DOI: 10.1088/0957-0233/2/10/006
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance-based instrumentation for multi-interface level measurement

Abstract: An electrical capacitance method is described for the measurement of multi-interface levels of gas/liquid/solid, including the foam layer. It uses a novel multi-electrode capacitance sensing element. A capacitance transducer based on the charge/discharge principle is used, which is stray immune and capable of operating at high frequencies to reduce t h e effects of the liquid conductivity on the measurement. The presence of foam is detected by processing the fluctuating component of the capacitance signal, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 2 publications
0
30
0
Order By: Relevance
“…Here, the measurement signals from each pair of capacitance sensors immersed in the layered system of phases generate a "capacitance profile" reflecting the actual distribution of phases in the vessel. Shi et al (1991) used a simpler approach, as shown in Fig. 12(b), in which an array of capacitance sensing electrodes was arranged on a single plate.…”
Section: Segmented Probesmentioning
confidence: 99%
“…Here, the measurement signals from each pair of capacitance sensors immersed in the layered system of phases generate a "capacitance profile" reflecting the actual distribution of phases in the vessel. Shi et al (1991) used a simpler approach, as shown in Fig. 12(b), in which an array of capacitance sensing electrodes was arranged on a single plate.…”
Section: Segmented Probesmentioning
confidence: 99%
“…Shi et al [2] presented a structure where electrode is removed and the capacitances are measured between the successive electrodes and . This method leads to a rather complex model to retrieve the level from the measured capacitances.…”
Section: Physical Aspectsmentioning
confidence: 99%
“…5) [4]. In this oscillator there is a linear relationship between the capacitance and the period (2) Using a multiplexer that is controlled by a microcontroller as has been suggested by Toth and Meijer [5], [6], the capacitances and can be selected independently. This results in the periods and , respectively.…”
Section: Capacitance Measurementmentioning
confidence: 99%
“…Furthermore, this kind of devices can be manufactured without requiring micromachining but directly by using deposition of a layer on a substrate and, therefore, they are compatible with any kind of technology. Some authors have analysed the influence of geometry of this kind of structures in the sensor performance [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%